The Influence of Perceived Trust, Service Quality and Perceived Risk: SME’s Interest in Using E-Commerce - Junedi Junedi; R. R. Wening Ken; Adibah Yahya; Debora Anastasya (Syntax Corporation Indonesia, 2022)
The rapid development of information and communication technology through digital marketing has a role in the development of the new economy marked by the phenomenon of e-commerce platform based business. This opportunity is certainly very attractive for SMEs to develop wider market access. By utilizing this sales channel, it has a positive effect on transaction value for business actors. This study aims to determine the extent to which the interest of SMEs in using e-commerce platform services. This research paper is based on a quantitative approach using interviews and observation of data collection with the participation of 100 SMEs.These results confirm the hypothesis that the development of the value of e- commerce transactions, which is formed by the interaction of business sites as an indicator of supply and internet user as an indicator of demand and supply, contribute to an increase in the intensity of macroeconomic activity.